Βιολογικό vs συμβατικό γάλα : οργανοληπτική εξέταση και ανίχνευση μικροσυστατικών - Χριστοφή, Χριστιάνα (Τμήμα Γεωπονικών Επιστημών, Βιοτεχνολογίας και Επιστήμης Τροφίμων,Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος,Τεχνολογικό Πανεπιστήμιο Κύπρου., 2012)
Milk has been, for centuries, one of the most basic foods in human daily nutrition. It plays an important role for growth and maintenance of the human body. Organic milk is a relatively new product to the market. During the last decade it has been used more often for the production of dairy products. The increasing demand for organic milk has let to the need of controlling its production and use, i.e. traceability and fraud (mixing with conventional milk). Therefore, it is necessary to find biomarkers, in order to distinguish organic from conventional milk. Reports have stipulated that Conjugated Linoleic Acid (CLA) could be used as a biomarker. However, reports on this subject are still limited; therefore more work needs to be done. The first thought when carrying out this work, was to check whether it is feasible by the consumers to distinguish between the two types of milk. The results of the Triangle Test confirmed that consumers do not realise the difference between the two types of milk. Because of this, it was decided to look for differences of micronutrients, that would be affected by the animal’s feeding regime. High performance liquid chromatography was used to determine the levels of vitamin E (atocopherol) in different types of milk (conventional vs. organic, cows vs. goats milk, raw vs. pasteurised).The results showed no statistical significant differences between the samples apart from a set of two samples, where the different characteristic was the animal type (cow vs. goat). As a conclusion, the content of vitamin E (a-tocopherol) in milk could be further examined as a possible biomarker in order to differentiate organic and conventional milk together with other micronutrients, like fatty acids (i.e. CLA).
Keywords: Milk; Milk--Analysis; Humans; Γάλα; Γάλα--Ανάλυση; Ανθρώπινος οργανισμός